Combating mixed messages: Promoting complementary feeding in Mumbai’s slums - Zahorsky, Meeghan; Dalal, Rupal; Athavale, Priyanka (International Food Policy Research Institute, 2015)
The Foundation for Mother & Child Health (FMCH) promotes effective complementary feeding practices through its First Thousand Days program, which aims to provide clear messaging through one-on-one counseling, courses, and home visits with pregnant and lactating mothers on complementary feeding practices. The objective of this program is to support proper growth and good health during the first 1,000 days of a child’s life, avoiding the common plague of undernutrition and malnutrition. This program was launched in 2006 by the foundation’s trustees and volunteers, and now has 25 full-time staff working at four clinics in Mumbai’s slums.